2016
DOI: 10.18632/oncotarget.10105
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of RET oncogene by naphthalene diimide-mediated gene promoter G-quadruplex stabilization exerts anti-tumor activity in oncogene-addicted human medullary thyroid cancer

Abstract: Medullary thyroid cancer (MTC) relies on the aberrant activation of RET proto-oncogene. Though targeted approaches (i.e., tyrosine kinase inhibitors) are available, the absence of complete responses and the onset of resistance mechanisms indicate the need for novel therapeutic interventions. Due to their role in regulation of gene expression, G-quadruplexes (G4) represent attractive targets amenable to be recognized or stabilized by small molecules. Here, we report that exposure of MTC cells to a tri-substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Indeed, though NDIs and RHSP4 are both able to bind with high affinity G4 DNA, affinity constants obtained by surface plasmon resonance analyses (for htel22 are: 99106 M À1 for RHPS4 and from 79106 M À1 to 3.19105 M À1 for the NDIs [29,[46][47][48]) suggested that the major difference between NDIs and RHPS4 may be related to the G4 selectivity. Interestingly, analysis of protein levels and gene expression (in particular for BCL2, Cyclin A and E, CDK2, PCNA, p21/ CDKN1A) indicated a diametrically opposite behavior between the two classes of ligands and suggested a different target spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, though NDIs and RHSP4 are both able to bind with high affinity G4 DNA, affinity constants obtained by surface plasmon resonance analyses (for htel22 are: 99106 M À1 for RHPS4 and from 79106 M À1 to 3.19105 M À1 for the NDIs [29,[46][47][48]) suggested that the major difference between NDIs and RHPS4 may be related to the G4 selectivity. Interestingly, analysis of protein levels and gene expression (in particular for BCL2, Cyclin A and E, CDK2, PCNA, p21/ CDKN1A) indicated a diametrically opposite behavior between the two classes of ligands and suggested a different target spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a large number of studies have exploited the naphthalene diimide (NDI) moiety as a G4‐binding motif, taking advantage of its synthetic accessibility, optoelectronic, G4 binding, and sensing properties . Tri‐ and tetrasubstituted NDIs have been broadly explored NDIs due to their potency and duplex versus G4 selectivity, and have proven to be effective cores for multimodal reactive and photoreactive NDI conjugates, and even targeting human medullary thyroid cancer . Tetrasubstituted NDIs have shown bimodal fluorescence and photocytotoxicity, high affinity for hTel G4 DNA, antiproliferative potency in pancreatic cancer cells and inhibition of telomerase activity …”
Section: Introductionmentioning
confidence: 99%
“…The involvement of G4 structures in several human diseases propelled the development of small molecules directed against G4s 9 . Aromatic cores with protonable side chains, such as the acridine, BRACO-19 49,50 and water-soluble naphthalene diimides (NDIs) 21,[51][52][53][54][55][56] , specifically bind the G4 conformation. So far, the vast majority of molecules has been tested against cellular G4s implicated in tumor pathogenesis: some compounds showed interesting antiproliferative properties 57 ; in particular, quarfloxin proceeded into phase II clinical trials, but its limited bioavailability prevented further progress 58 .…”
mentioning
confidence: 99%